A Randomized Controlled Trial of an Integrated Brain, Body, and Social Intervention for Children With ADHD. Issue 5 (March 2020) - Smith, Stephanie D.; Vitulano, Lawrence A.; Katsovich, Liliya; Li, Shuaixing; Moore, Christina; Li, Fenghua; Grantz, Heidi; Zheng, Xixi; Eicher, Virginia; Aktan Guloksuz, Selin; Zheng, Yi; Dong, Jinxia; et al.
Objective: This study evaluated the efficacy of an Integrated Brain, Body, and Social (IBBS) intervention for children with ADHD. Treatment consisted of computerized cognitive remediation training, physical exercises, and a behavior management strategy.Method: Ninety-two children aged 5 to 9 years with ADHD were randomly assigned to 15 weeks of IBBS or to treatment-as-usual. Primary outcome measures included blinded clinician ratings of ADHD symptoms and global clinical functioning. Secondary outcome measures consisted of parent and teacher ratings of ADHD and neurocognitive tests.Results: No significant treatment effects were found on any of our primary outcome measures. In terms of secondary outcome measures, the IBBS group showed significant improvement on a verbal working memory task; however, this result did not survive correction for multiple group comparisons.Conclusion: These results suggest that expanding cognitive training to multiple domains by means of two training modalities does not lead to generalized improvement of ADHD symptomatology.